Constant magnetic field in treating congenital esophageal and anorectal malformation: a review - Shiqi Liu; Yi Lv (BMJ Publishing Group, 2020)
Background Congenital esophageal and anorectal malformation are common in neonates. Refractory esophageal anastomotic stricture and abnormal defecation after surgical correction in infants are challenging surgical problems. Magnetic compression anastomosis (MCA) using mated magnets with their interposed compressed tissue may result in serosa-to-serosa apposition.Data sources A literature search was performed to establish an algorithm for these accidents by the authors to identify relevant articles published from 1977 to 2019 in Google, Medline, ISI Web of Knowledge Ovid, CNKI and library document delivery, using search terms "magnetics", "esophageal malformation", "anorectal" and "perforation". A total of 24 literatures were collected.Results Magnamosis is technically feasible for alimentary tract anastomoses in pediatric patients. The magnets are most commonly made of neodymium-iron-boron and samarium-cobalt alloys, which have been employed to create solid anastomosis for long-gap esophageal atresia and refractory esophageal stricture without thoracotomy in children in recent years. Furthermore, magnamosis can be used for the functional undiversion of ileostomy. In anorectal malformations with favorable anatomy, this procedure may avoid an operative repair such as posterior sagittal reconstruction.Conclusion Translumenal anastomosis of digestive tract using the MCA is a reliable, minimally invasive and feasible method to treat congenital esophageal and anorectal malformation.